Advanced airway training in the UK: A national survey of senior anesthetic trainees - Adam J Boulton; Sunita R Balla; Aleksandra Nowicka; Thomas M Loka; Cyprian Mendonca (Wolters Kluwer Medknow Publications, 2019)
Background and Aims: High-quality training in advanced airway skills is imperative to ensure safe anesthetic care and develop future airway specialists. Modern airway management skills are continually evolving in response to advancing technology and developing research. Therefore, it is of concern that training provisions and trainee competencies remain current and effective. Material and Methods: A survey questionnaire based on the airway competencies described in the Royal College of Anaesthetists' curriculum and Difficult Airway Society guidelines was posted to all United Kingdom (UK) National Health Service hospitals to be completed by the most senior anesthetic trainee (ST 5-7, resident). Results: A total of 149 responses were analyzed from 237 hospitals with eligible anesthetic trainees (response rate 63%), including 53 (36%) and 39 (26%) respondents who had completed higher and advanced level airway training respectively. Although clinical experience with videolaryngoscopy was satisfactory, poor confidence and familiarity was identified with awake fiberoptic intubation, high frequency jet ventilation, at risk extubation techniques, and airway ultrasound assessment. Only 26 (17%) respondents had access to an airway skills room or had regular airway emergency training with multidisciplinary theater team participation. Reported barriers to training included lack of training lists, dedicated teaching time, experienced trainers, and availability of equipment. Conclusions: This national survey identified numerous deficiencies in airway competencies and training amongst senior anesthetic trainees (residents) in the UK. Restructuring of the airway training program and improvements in access to training facilities are essential to ensure effective airway training and the capability to produce future airway specialists.